The Importance of Development in the Education Process - Siti Mimbi Salmani; Muhibbin Syah; Bambang Samsul Arifin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Basically, humans in their life journey always coexist with the educational process, each phase of their development period has its own characteristics and is not the same. So it requires different teaching methods in each phase. Psychology in education helps analyze these developments, so that they can comply with educational goals in order to achieve scientific targets according to their age. Not only that, teachers also find it difficult to determine the level and criteria for achieving assessments. To make it, teachers must create derived criteria from the material taught based on goals and expectations. Apart from guiding the goals and expectations of teaching materials, teachers also need to adapt to the various abilities of students so that the existing criteria are appropriate to the circumstances. This analysis stage is still in the early stages and of course requires a lot of time.